Analisa Perilaku Rumah Tangga: Preferensi, Fertilitas, Alokasi Waktu dan Tawar Menawar - Wicaksono, Teguh Yudo (UI Scholars Hub, 2004)
Economic scholars in Indonesia tends to focus more on market rather than household behavior. This could be caused by their assumption that household behavior often irrational from conventional economic perspective. This paper argues that irrationality behavior is not proven empirically. It is shown that the behavior is economic deterministic; like preference on their child's gender, time allocation and bargaining process in household. The result shows that females are more preferred than males and this can be explained by economic logic. Nevertheless, position and bargaining power of females still weak in household. It has proven empirically by some estimation methods with some restrictions. The final objective is the integration of economic science with other social sciences in household behavior analysis in Indonesia.